Knowledge, attitude and practice regarding nursing interruptions among Chinese nurses: A nationwide cross-sectional survey - Jianfei Xie; Qian Sun; Siyuan Tang; Siqing Ding; Zhuqing Zhong; Sainan Zeng; Yinglong Duan; Xiangyan Zhang; Andy SK. Cheng (Elsevier, 2020)
Objectives: To explore the knowledge, attitude and practice of Chinese nurses regarding nursing interruptions and related factors. Methods: A total of 6,400 nurses from 31 hospitals in China were investigated by using the Knowledge, Attitude and Practice (KAP) Questionnaire of Nursing Interruptions. The questionnaire consists of three dimensions, knowledge, attitude and practice, containing 10, 9 and 7 items, with full score of 50, 45 and 28, respectively. Results: The mean overall KAP score regarding nursing interruptions of Chinese nurses was 74.05 ± 16.65 (range: 26-123), with scores for the knowledge, attitude, and practice component being 21.74 ± 9.80, 34.83 ± 6.98, and 17.49 ± 4.97, respectively. Among the nurses, 70.8% of them experienced an average level of KAP toward nursing interruptions while 15.5% were at a poor level. The knowledge, attitude, and practice of nursing interruptions were better in chief nurses, managers, nurses with a master degree or above, nurses ever received training, and nurses with a strong agreement to leadership compared to nurses in other groups (P < 0.05). In addition, employment type, professional title, position, standardized training and leaders' attention were predictors of KAP in nurses. Conclusion: Chinese nurses have a moderate level of KAP regarding nursing interruptions. Leaders' attention, standardized training, position, professional title and employment type could predict nurses' KAP state of nursing interruptions. Thus, a targeted training program should be implemented for clinical nurses by nursing leaders, with a particular focus on feasibility and professionalism. Keywords: Attitude, Knowledge, Nursing, Nursing interruptions, Practice, Questionnaires